Sleep Characteristics, Magnetic Resonance Imaging- and Dual-Energy X-Ray Absorptiometry-Based Morphological Parameters, Muscle Strength, and Risk of Falls in Sedentary Older Subjects. - Borghi, Stefano; La Torre, Antonio; Messina, Carmelo; Sconfienza, Luca M.; Banfi, Giuseppe; Vitale, Jacopo A. (Journal of Aging & Physical Activity, 2025)
Background: The aims of this cross-sectional study were to (a) assess actigraphy-based sleep parameters (total sample and gender differences), (b) assess differences in morphological parameters and physical function between short- versus normal-sleepers and poor- versus good-sleepers, and (c) assess the possible correlations between sleep variables and morphological and physical function parameters in older subjects. Methods: This study enrolled 42 healthy older participants (60–80 years). Participants completed the following clinical evaluations: (1) whole-body dual-energy X-ray absorptiometry to assess the appendicular skeletal muscle mass index; (2) magnetic resonance imaging acquisition to determine the cross-sectional muscle area of thigh muscles and intermuscular adipose tissue; (3) risk of fall assessment through the mini-Balance Evaluation Systems Test; (4) strength assessment: (a) chair stand test and (b) handgrip strength test; (5) sleep monitoring by actigraphy to assess total sleep time, sleep efficiency, wake after sleep onset, sleep latency, fragmentation index, mobile time, and subjective sleep quality. Results: 31.0% of subjects were short-sleepers (total sleep time < 6 hr), 19.1% were poor-sleepers (sleep efficiency < 85%), and gender differences were detected in mobile time (males: 15.8 ± 6.0 and females: 13.4 ± 6.8; p <.001) and fragmentation index (males: 35.3 ± 14.3 and females: 29.6 ± 14.6; p <.001); no significant differences were observed between groups (short- vs. normal-sleepers and poor- vs. good-sleepers) in morphological and physical function variables; correlation analysis showed that sleep latency negatively correlated with Mini-Balance Evaluation Systems Test (r = −.352; p =.022) and a positive correlation was detected between cross-sectional muscle area and mobile time (r =.349, p =.023). Conclusion: No differences were observed in morphological and function parameters between good- versus poor-sleepers, those subjects with worse sleep onset latency (i.e., longer time to fall asleep) registered higher for risk of fall. The potential role of sleep in the physiological mechanisms of muscular aging must be explored through cross-sectional cohort studies with a larger population.